The law in Euripides’ Medea - Giombini, Stefania (Revista Archai, 2017)
This paper investigates appeals to law in Euripides’ Medea, dramatic elements which seem to point to two distinct aspects in the development of Greek Law. The text seems to appeal to: a) archaic law when the oath appears adequate (or sufficient) to establish wedlock, and b) classical law with respect to other aspects of familial jurisprudence. I argue that Euripides has intentionally contrasted these legal perspectives as part of a larger contrasting narrative. Euripides begins by introducing the essentials features of the myth of Medea in terms of its archaic context. In the latter half, he then in turn contrasts this narrative with contemporary views, and thus offers a critical reflection upon his own culture and society. These contrasting narratives are further supported by highlightening an important transition in the text, which focuses on Themis and Dike and the importance of laws.